Sustainable Tea at Ambootia: A Case Study - Choudhary, Puneet; Srivastava, Manish (AMC Indian Journal of Entrepreneurship, 2017)
Nestled amid the lush green hills of Kurseong in the Darjeeling district of West Bengal, Ambootia, is a family owned tea estate that has a long tradition of working with nature and not against it. Established by the British in the mid-19th century Ambootia was famous for producing some of the best Darjeeling teas till the 1960s and 70s. But, by the 1980s, tea quality and yield started declining due to neglect and heavy dependence on chemical farming. In 1985, its annual production fell to 100 tonnes from about 250 tonnes earlier; the estate was on the verge of financial ruin. This case discusses the turnaround of the Ambootia group from near bankruptcy in 1984 - 85 as being a signature label found in exclusive stores found all around the world today.